The practical landscape and optimal incentives of government purchasing public sports services from the perspective of incomplete contracts – an empirical analysis - Ding Lu; Zan Zhang; Bo Zang (Journal of Public Procurement, 2026)
Purpose This study aims to analyse incomplete-contract dilemmas in the government procurement of public sports services. It empirically tests how contractual completeness drives project implementation, builds an incomplete-contract embedded principal-agent model and designs a three-stage full-lifecycle incentive framework to boost supply efficiency and Pareto public sports resource allocation. Design/methodology/approach Based on incomplete contract and principal-agent theories, this study adopts textual analysis and descriptive statistics of 128 sports Public–Private Partnership samples. Binary Logistic and Probit regressions were used for the baseline and multi-angle robustness checks, while a tailored principal-agent model was developed to derive the equilibrium optimal incentive solutions. Findings Public sports procurement exhibits incomplete contract flaws across all phases. Contractual completeness dominates external factors in boosting project success and increasing private effort and social welfare. Fixed payments serve as a backup for incomplete contracts, with a diminishing marginal value when the terms are well-specified. Without clear operational content, the viability gap subsidies and government payments become misaligned guarantees of minimum returns. This study builds a principal-agent model to unpack its transmission path and proposes a three-transaction-cost full-cycle incentive framework for refined contract governance. Social implications This study provides practical guidance for optimising government public sports service procurement, helping improve service quality and efficiency, safeguarding public interests and promoting the healthy development of the public sports service system. Originality/value It integrates two core contract theories to fill the micro-contractual governance gap in public sports PPP research. This study offers large-sample quantified empirical evidence and delivers actionable staged clause optimisation schemes for public service procurement governance.